War and Order in Eighteenth Dynasty Egypt (1550‒1295 BCE) - Allon, Niv (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
This paper studies royal inscriptions of the Eighteenth Dynasty—a period of extensive military activity in Nubia and the Levant—to examine the prevailing assumption that earthly wars were conceived as mirroring a cosmic struggle between order and chaos. Instead, the sources suggest a more intricate picture, in which royal prerogative and divine will are at play, often ambiguously intertwined.